Exploration of terrestrial planets from spacecraft instrumentation, investigation, interpretation - Surkov, Y. A. (Yuri Aleksandrovich) (Wiley-Praxis series in astronomy and astrophysics, 1997)
This book is divided into two parts. In Part I, the author describes the evaluation of the Solar System from the earliest stages to the formation of the planets and differentiation of their material. He then discusses the nature, composition and properties of Mercury, Venus, the Moon and Mars and several planetary satellites. In Part II, the author gives a comprehensive overview of the methods and instrumentation which have been utilized in spacecraft studies of these bodies, including gamma-ray and X-ray spectrometry, neutronmetry, alpha-particle spectrometry and mass spectrometry.